2007
DOI: 10.1021/jp073031q
|View full text |Cite
|
Sign up to set email alerts
|

A Solution Study on the Local and Global Structure Changes of Cytochrome c:  An Unfolding Process Induced by Urea

Abstract: The local and global structural changes of cytochrome c induced by urea in aqueous solution have been studied using X-ray absorption spectroscopy (XAS) and small-angle X-ray scattering (SAXS). According to the XAS result, both the native (folded) protein and the unfolded protein exhibit the same preedge features taken at Fe K-edge, indicating that the Fe(III) in the heme group of the protein maintains a six-coordinated local structure in both the folded and unfolded states. Furthermore, the discernible differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Immersion into 8 M urea solutions disrupts the hydrogen bonds which stabilize the cytochrome c's tertiary structure and leads to unfolding of the molecule. 24 Small angle x-ray data 25 of the unfolded cytochrome c at pH 7 reveal a structural transition from the almost spherical conformation of the folded protein (semi-major axis 18 Å, semi-minor axis 18 Å, radius of gyration R g = 12.8 Å) to an eccentric ellipsoid shape (semimajor axis 65 Å, semi-minor axis 9 Å at 8 M urea and R g = 29.7 Å at 10 M urea).…”
Section: Experimental Cytochrome Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Immersion into 8 M urea solutions disrupts the hydrogen bonds which stabilize the cytochrome c's tertiary structure and leads to unfolding of the molecule. 24 Small angle x-ray data 25 of the unfolded cytochrome c at pH 7 reveal a structural transition from the almost spherical conformation of the folded protein (semi-major axis 18 Å, semi-minor axis 18 Å, radius of gyration R g = 12.8 Å) to an eccentric ellipsoid shape (semimajor axis 65 Å, semi-minor axis 9 Å at 8 M urea and R g = 29.7 Å at 10 M urea).…”
Section: Experimental Cytochrome Cmentioning
confidence: 99%
“…At pH 4.4, we observe a surface coverage of 1.06 •10 −12 mol/cm 2 and a volume packing density of 5.6%. We obtain the respective values for the unfolded protein using the x-ray scattering data of Hsu et al 25 In 8 M urea solutions, each molecule has a volume of V u = 22 nm 3 and takes up 23.4 nm 2 when adsorbed on a surface. The theoretical monolayer would thus contain 7 • 10 −12 mol/cm 2 .…”
Section: Ph-dependent Cytochrome C Adsorptionmentioning
confidence: 99%
“…It can provide coordination numbers and distances between absorbing atom and surrounding atoms within 5 Å. 30 The range above the rising edge up to 40 eV including the pre-edge peaks is named XANES. In the XANES regime, the spectrum features are dominated by the contributions of multiple scattering events with many atoms, which is a measurement of high-order atomic correlation functions.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the optical spectroscopies mentioned, small-angle x-ray scattering (SAXS) can be a more direct tool in extracting global structural information of proteins in unfolding (7,8). Recent studies have shown the apparent advantage of combining global and local structural tools in addressing correlations between the local-local structures and local-global structures (9)(10)(11); with this information, a better description of the protein unfolding process as well as a better understanding of intermediate states or partially folded structures can be expected.…”
Section: Introductionmentioning
confidence: 99%